'Click' generated 1, 2, 3-triazole based organosulfur/selenium ligands and their Pd(ii) and Ru(ii) complexes: their synthesis, structure and catalytic applications. Issue 28 (24th June 2016) - Kumar, Satyendra; Saleem, Fariha; Singh, Ajai K.
Abstract : Sonogashira and Suzuki–Miyaura coupling were catalyzed with Pd(ii ) complexes (0.001–2 mol%), and transfer hydrogenation (in water–glycerol) was catalyzed with Ru(ii ) complexes (≤0.4 mol%). Abstract : 1-(2, 6-Diisopropylphenyl)-4-(phenylthio/selenomethyl)-1 H -1, 2, 3-triazole (L1 /L2 ) was synthesized by a 'Click' reaction and treated with [Pd(CH3 CN)2 Cl2 ] for 5 h or [(η 6 -C6 H6 )RuCl(μ-Cl)]2 for 8 h (followed by reaction with NH4 PF6 ) at room temperature, resulting in complexes [Pd(L )Cl2 ] (1 and2 ) or [(η 6 -C6 H6 )Ru(L )Cl]PF6 (3 and4 ) (L =L1 orL2 ), respectively. The four complexes (1–4 ) and ligands (L1 andL2 ) were characterized with 1 H, 13 C 1 H and 77 Se 1 H NMR spectroscopy and high resolution mass spectrometry. The single crystal structures of1–4 were solved. The geometry of Pd in1 and2 is distorted square planar. The Pd–S and Pd–Se bond distances in1 and2 are 2.277(3) and 2.384(6) Å respectively. In3 and4, there is a pseudo-octahedral "piano-stool" type disposition of donor atoms around Ru. The Ru–S and Ru–Se bond lengths in3 and4 are 2.3728(12) and 2.4741(6) Å respectively. The catalytic activity of complexes1 and2 was explored for Suzuki–Miyaura coupling (SMC) in water and the Sonogashira coupling reaction. For various aryl bromides, including deactivated ones, complexes1 and2 were found to be efficient catalysts for both couplings. The optimum loading of1 and2 required to catalyze both coupling reactions is of the order of 0.001–2 mol% of Pd. For SMC, no additive or phase transfer catalyst was added. For catalysis of the transfer hydrogenation (TH) of aldehydes and ketones, the half-sandwich Ru(ii ) complexes3 and4 were explored. Their optimum catalytic loading was found to be 0.1–0.4 mol% of Ru. For TH, both the water solvent and the glycerol hydrogen source are environmentally friendly. The catalytic efficiencies of3 and4 are comparable with those reported for other catalysts for TH carried out with 2-propanol or glycerol as a H-source.1, with a sulfur ligand, is more efficient than2 (Se analog) for both SMC and the Sonogashira coupling. The activities of3 and4 for TH are in the order Se > S.